Autonomous Soil Water Content Sensors Based on Bipolar Transistors Encapsulated in Porous Ceramic Blocks - Carvalhaes-Dias, Pedro; Morais, Flavio J. O. [UNESP]; Duarte, Luis F. C.; Cabot, Andreu; Siqueira Dias, J. A. (Mdpi, 2019)
We present an autonomous sensor to measure soil water content that uses a single heat pulse probe based on a transistor encapsulated in a porous block. The sensor uses a bipolar junction transistor, which performs as both a heating and temperature-sensing element. Since the sensor depends on a porous block to measure the matric potential of the soil, it does not suffer from accuracy problems if the contact between the probe and the soil is not perfect. A prototype of the sensor showed a temperature variation of Delta T=2.9 degrees C when the porous ceramic was saturated with water. The sensor presented an almost linear behavior for small changes in the matric potential of a red latosol when tested in the 1-kPa and 35-kPa pressure range, showing a sensitivity of S=0.015 degrees C/kPa. The ultra-low power signal conditioning circuit can read the sensor's temperature with a resolution of approximately 0.02 degrees C, so the matric potential can be read in increments of at least 1.33 kPa. When powered only by a 2-F supercapacitor from the energy-harvesting system, the interrogation circuit is able to take one soil water content measurement per day, for eleven days.
Keywords: soil water content; porous ceramic; bipolar transistor; embedded circuits; heat dissipation soil moisture sensors; low-power circuits